Association between paternal age and subtypes of preterm birth: a retrospective study. Issue 6 (June 2022) - Mao, Yiting; Liu, Zhaonan; Zhang, Chen; Wang, Yinyu; Meng, Yicong; Chen, Lei; Sheng, Jianzhong; Wu, Yanting; Huang, Hefeng
Abstract: Research question: Is advanced paternal age (APA) associated with preterm birth overall and with the subtypes of preterm birth? Design: A total of 66, 167 pregnancies were included. Linear regression and logistic regression models were used to analyse the association between paternal age and subtypes of preterm birth. Results: APA was associated with a higher risk of preterm birth (35–44 years: odds ratio [OR] 1.16 [1.04–1.28], P = 0.006; >44 years: OR 1.40 [1.10–1.78], P = 0.007) and very early preterm birth (VPTB; <34 weeks) (35–44 years: OR 1.46 [1.17–1.81], P = 0.002; >44 years: OR 1.65 [1.01–2.69], P = 0.045). The increased risk of preterm birth was mostly associated with preterm birth with premature rupture of membranes (PROM-PTB) (35–44 years: OR 1.23 [1.03–1.48], P = 0.021) and medically induced preterm birth (MI-PTB) (>44 years: OR 1.55 [1.12–2.15], P = 0.008). For women who carried a male fetus, having the father in the 35- to 44-year-old group carried a 1.29-fold risk of PROM-PTB (OR 1.29 [1.02–1.63], P = 0.031) and a 1.26-fold risk of MI-PTB (OR 1.26 [1.04–1.52], P = 0.017). There was no evidence of a higher risk of PROM-PTB among women carrying a female fetus, but there was a 1.67-fold higher risk of MI-PTB for the 45-or-older paternal age group (OR 1.67 [1.04–2.67], P = 0.035). Conclusions: These results suggest that APA is associated with a higher risk of preterm birth and VPTB, mainly related to PROM-PTB and MI-PTB. The study also indicates a fetal sex-specific association between APA and a higher risk of PROM-PTB for male fetuses.